Sustainable construction : green building design and delivery - Kibert, Charles J. (United Kingdom John Wiley & Sons,LTD, 2022)
"The rapidly evolving and exponentially growing green building movement is arguably the most successful environmental movement in the United States today. Sustainable building has proven to yield substantial environmental and economic advantages. Green buildings are designed, built, and operated at a high level of energy and water efficiency, appropriate use of land and landscaping, use environmentally friendly materials, with special attention to life cycle. According to the World Green Building Trends 2018 SmartMarket Report by Dodge Data and Analytics in partnership with USGBC, a survey of over 2,000 participants from 87 countries, shows that global green building activity continues its ascent with almost half of total respondents expecting to build more than 60% of their projects as green buildings by 2021. More than half of respondents believe that rating systems such as LEED provide rigorous third-party verification that ensures buildings operate sustainably. The top triggers globally for green building activity are client demand, environmental regulation and occupant health"--
Keywords: Sustainable construction; Sustainable buildings -- Design and construction; Green technology; Sustainable architecture